A gender-based analysis of nonmedical prescription opioid use among people who use illicit drugs. (October 2019) - Cheng, Tessa; Nosova, Ekaterina; Small, Will; Hogg, Robert S.; Hayashi, Kanna; DeBeck, Kora
Abstract: Background: Research investigating the unique impacts associated with engaging in nonmedical prescription opioid use (NMPOU) among males and females who also use illicit drugs is needed. Methods: Data were collected between 2013 and 2017 from two linked prospective cohort studies in Vancouver: the At-Risk Youth Study and Vancouver Injection Drug Users Study. Generalized estimating equations were used to identify factors associated with engaging in NMPOU among females and males separately. Results: Among 1459 participants, 534 were female (37%). Similar proportions of females (46%) and males (48%) engaged in NMPOU at their first visit during the study period. In multivariable analyses, factors associated with NMPOU among both males and females included heroin use, overdose, drug dealing, and difficulty accessing health and social services. Among females, those who engaged in NMPOU were more likely to report Caucasian or white ethnicity, cocaine use, crystal methamphetamine use, and sex work; among males, those who engaged in NMPOU were older, reported crack use and engaged in binge drug use (all p < 0.05). Conclusion: The prevalence of NMPOU was similar among males and females who use illicit drugs in Vancouver, and NMPOU was independently associated with markers of vulnerability among both genders. Findings highlight the need for a comprehensive public health approach to address NMPOU that integrates overdose prevention and reversal services, employment opportunities, and better access to services for both women and men. Highlights: The prevalence of nonmedical prescription opioid use (NMPOU) was similar for males (48%) and females (46%) Illegal drug use, overdose, drug dealing, and difficulty accessing services were associated with NMPOU among both sexes Findings highlight the need for a comprehensive public health approach to address NMPOU among women and men